Digital Documentation—A Nonprioritized Subject in Higher Nursing Education. A Qualitative Study With Educators. - Eriksson, Björn; Svartengren, Magnus; Dahlgren, Anna; Lindblom, Jessica; Arakelian, Erebouni (Journal of PeriAnesthesia Nursing, 2026)
To explore how educators in postgraduate nursing programs in anesthesia care, operating room care, and intensive care nursing—both in academic and clinical settings—experience teaching digital documentation in theory and practice. Qualitative descriptive study using thematic analysis by Braun and Clarke. Individual interviews were conducted between April and August 2023 with 12 participants, including faculty members at the universities and clinical supervisors (10 women, 2 men). The participants were between 37 and 72 years of age (mean, 52 years) and had between 1 and 15 years (mean, 6 years) of work experience. Two themes were identified: (1) "Faculty members' contradictory attitudes and opinions regarding the content, importance, and need for documentation in patients' electronic medical records in perioperative care" and (2) "The relationship between universities, healthcare providers, and individuals." Subthemes included the lack of consensus on teaching digital documentation, factors influencing successful teaching, prioritizing patient-oriented competencies and tasks, and viewing documentation as a potential obstacle to care. The topic of documentation is often a low priority. Higher education and clinical practice lack a consensus on the purpose, content, and methods for teaching documentation. Thus, greater attention is needed to clarify the purpose of documentation, particularly digital documentation, and to define relevant teaching content. Digital competence can better prepare students for future work and reduce technostress. The goal should be to narrow the gap between "work as imagined" and "work as done."